Design of an Uninterrupted Power Supply with Li-Ion Battery Pack: A Proposal for a Cost-Efficient Design with High Protection Features - Thealfaqar A. Abdul-jabbar; Adel A. Obed; Ahmed J. Abid (Journal of Techniques)
While decreasing their cost, lithium-ion batteries began to enter a vast domain for energy storage field, including solar systems and electric vehicles, due to their high energy density compared to other types. Besides, li-ion batteries require a safe and secure ground to reach the best performance and decrease the explosion risk. The safe operation of the battery is based on the main protection features and balancing the cells. This study offers a battery BMS design that protects li-ion batteries from overcharging, over-discharging and overheating. It is also offering passive cell balancing, an uninterrupted power source to load, and monitoring data. The used controller is Arduino mega 2560, which manages all the hardware and software protection features. Software features that include 1) variable charging speed according to the batteries charging status, 2) measuring the batteries state of health and state of charge, 3) controlling the uninterrupted driver, 4) regulating the charge and discharge voltage, and 5) measure and display all readings.